A Bridging the Digital Divide in Education: Disparities in Google Classroom Utilization and Technical Challenges among Urban and Rural Teachers - Astari; Yulianto, Dwi (Universitas Pendidikan Ganesha, 2025)
The digital divide remains a serious obstacle to the implementation of online learning in Indonesia. The inequality of access to Information and Communication Technology (ICT) is clearly visible, where urban areas have much better digital infrastructure than rural areas. This study aims to analyze the differences in supporting factors for online learning between secondary school teachers in areas with contrasting geographical characteristics, especially related to network connections, technical constraints, school infrastructure, and the use of Google Classroom. A total of 395 teachers participated in an online survey using a closed questionnaire consisting of 22 items. Data analysis through descriptive statistics and t-tests showed that teachers in rural areas faced higher technical constraints and lower utilization of Google Classroom compared to teachers in urban areas. This study provides an empirical contribution to mapping the dimensions of the digital divide between regions and emphasizes the urgency of region-based strategies, such as adaptive digital literacy training and proportional device distribution. These results can be used as a basis for formulating more inclusive and equitable education policies in the digital era.